FORECAST OF VOLUMES OF LOSSES OF OIL IN CASE OF ORIGIN OF EMERGENCY SITUATION - Возняк, Мирослав Петрович; Кривенко, Галина Мирославівна; Возняк, Лідія Володимирівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Main oil pipelines are the objects of increased hazard. The system of main oil pipelines entered in the period of refuses that result in accidents. Forecast of volumes of possible discharges through the orifices in the body of pipe is given. Computers model the flow of oil through the forecast orifices gives the direction and covered of oil area.